2015
DOI: 10.1016/j.nicl.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physiological MRI correlates of occult cerebrovascular disease in late-onset epilepsy

Abstract: Late-onset epilepsy (LOE), with onset after 50 years of age, is often attributed to underlying occult cerebrovascular disease. LOE is associated with a three-fold increase in subsequent stroke risk, therefore it is important to improve our understanding of pathophysiology. In this exploratory study, we aimed to determine whether established structural magnetic resonance imaging markers and novel physiological imaging markers of occult cerebrovascular disease were more common in patients with LOE than age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Our results revealed that IGE patients with absence seizures showed prolonged ATT in the left superior temporal gyrus. This finding is consistent with a recently published study that found that patients with late-onset epilepsy have significantly prolonged ATT in widespread brain regions, but the greatest prolongation is predominantly distributed in the temporal and frontal lobes 20 . The authors considered that the prolongation of ATT may be attributable to the recruitment of secondary collaterals induced by seizure activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results revealed that IGE patients with absence seizures showed prolonged ATT in the left superior temporal gyrus. This finding is consistent with a recently published study that found that patients with late-onset epilepsy have significantly prolonged ATT in widespread brain regions, but the greatest prolongation is predominantly distributed in the temporal and frontal lobes 20 . The authors considered that the prolongation of ATT may be attributable to the recruitment of secondary collaterals induced by seizure activity.…”
Section: Discussionsupporting
confidence: 93%
“…The technique has been employed successfully in cerebrovascular diseases, such as acute ischemic stroke 18 and moyamoya disease 15 , which demonstrates significant correlations between multi-delay ASL and dynamic susceptibility contrast (DSC) as well as computed tomography (CT) perfusion CBF measurements. In addition, a recent study using this protocol found no significant differences in CBF and significantly prolonged ATT between patients with late-onset epilepsy and control subjects 20 . The authors considered that the prolonged ATT may be attributable to the recruitment of secondary collaterals induced by seizure activity.…”
mentioning
confidence: 77%
“…haematoma size) does not support this hypothesis. Alternatively, injury secondary to CSVD (both micro-and macro-structural) may act independently on delayed seizure risk (Gibson et al, 2014;Hanby et al, 2015). Finally, a combination of the two mechanisms described above cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Late-Onset Epilepsy (LOE), with onset in adult life, is often attributed to cerebrovascular disease and intracranial tumor [1]. While our patient indicated a rare cause, which is the Linear Scleroderma en Coup de Sabre (LScs).…”
Section: Introductionmentioning
confidence: 70%